Analisis Penggunaan Cathodic Protection dengan Metode Sacrificial Anode Sebagai Pengendalian Korosi Pipa Minyak 16 Inci PT. Chevron Pacific Indonesia Simp. Perawang-Minas Area - Dedy Masnur; Eko Saputra; Putri Nawangsari (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2023)
Cathodic protection is a thermodynamic corrosion control method using metal as the cathode. There are two methods of cathodic protection, namely Sacrificial Anode Cathodic Protection (SACP) and Impressed Current Cathodic Protection (ICPP). This study will analyze the use of Cathodic Protection with the Sacrificial Anode method as corrosion control on a 16 inch oil pipe at PT. Chevron Pacific Indonesia. Carbon steel pipe (API 5L Grade B) with cast magnesium anode material. Calculation of anode requirement for corrosion prevention will be compared with actual field data within 10 years. The calculation results show that the number of calculation parameters used affects the results of the anode requirement on an oil pipe with a length of 16 meters, a diameter of 16 inches, anode with a length of 0.648 m, net weight of anode 7.7 Kg, magnesium anode material with an anode output of 10.8 A/m2, anode density 1765 Kg/m3, wear and tear (volume) 2296 x 10-3 m3 A/y, and a life time of 10 years. Theoretical calculations get 6 anode rods while the actual data requires 8 anode rods.